Synchronous Langat Virus Infection of Haemaphysalis longicornis Using Anal Pore Microinjection - Talactac, Melbourne; Yoshii, Kentaro; Hernandez, Emmanuel; Kusakisako, Kodai; Galay, Remil; Fujisaki, Kozo; Mochizuki, Masami; Tanaka, Tetsuya (Viruses, 2017)
The tick-borne encephalitis virus (TBEV) serocomplex of flaviviruses consists of arboviruses that cause important diseases in animals and humans. The transmission of this group of viruses is commonly associated with tick species such as Ixodes spp., Dermacentor spp., and Hyalomma spp. In the case of Haemaphysalis longicornis, the detection and isolation of flaviviruses have been previously reported. However, studies showing survival dynamics of any tick-borne flavivirus in H. longicornis are still lacking. In this study, an anal pore microinjection method was used to infect adult H. longicornis with Langat virus (LGTV), a naturally attenuated member of the TBEV serocomplex. LGTV detection in ticks was done by real-time PCR, virus isolation, and indirect immunofluorescent antibody test. The maximum viral titer was recorded at 28 days post-inoculation, and midgut cells were shown to be the primary replication site. The tick can also harbor the virus for at least 120 days and can successfully transmit LGTV to susceptible mice as confirmed by detection of LGTV antibodies. However, no transovarial transmission was observed from the egg and larval samples. Taken together, our results highly suggest that anal pore microinjection can be an effective method in infecting adult H. longicornis, which can greatly assist in our efforts to study tick and virus interactions.